PENGARUH PENDEKATAN KONSTRUKTIVISME TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEKS BIOGRAFI - artawan, Gede (Journal of Education Reseach and Evaluation, 2017)
The purpose of this peneitian is to know the influence of constructivism approach to learning in the learning activity biographical text on eighth grade students at SMP Harapan Nusantara. To determine the effect of using constructivism approach to the learning outcomes in learning biography text in class VIII in SMP Harapan Nusantara. To determine the effect of using constructivism approach to the activities and achievement in learning biography text in class VIII in SMP Harapan Nusantara. Collecting data in this study conducted by the method of observation and testing methods / giving tasks to create a text biography. Observation methods used to assess student learning activities and testing methods used to assess student learning outcomes. In the test methods exist in the form of the initial test or pre-test, in the form of tests made text biography and post-test method is given at the end of the study. Final test or post-test given immediately after the students are given learning biography text using constructivism approach the experimental class and the control class conventional model. Based on test results obtained multivariate statistical values Pillai, Strace Wilk's Lambada Hotelling's Trace, and Roy'sLargest Root each with Fhitung = 50, 720 with significance = 0.05 dba = 2 and obtained Ftabel dbd = 80 = 3, 232 at the 5% significance level. From the data obtained by analysis of F larger than F table, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. From the analysis of the data to test the hypothesis using multi-variate statistical variance of the activity and student learning outcomes can be concluded using kosntruktivisme approach has a significant effect on activity and learning outcomes in learning biography text in class VIII in SMP Harapan Nusantara.